PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN CARA BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN KELAS XI P1 DI SMA NEGERI 1 PEMATANGSIANTAR TAHUN AJARAN 2024/2025 - Lamsahat Tua Siahaan; Sepriandison Saragih; Marthin Fransisco Manihuruk (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine whether ther is an influence of problem based learning and learning method on student learning achievement in citizenship education subject for class XI P1 at SMA Negeri 1 Pematang Siantar academic year 2024/2025. The problem in this research is the influence of problem based learning dan learning method on student learning achievement in the citizenship education subject class XI P1 at SMA Negeri 1 Pematang Siantar for the 2024/2025 academic year.The population and sample in this study were all 36 students of class XI P1. The instrument used are questionnaires and documentation. The quality of research instrument for questionnaires and student learning achievement is assessed through validity and reliability tests. All data from the three variables above were first tested whether they were normally distributed or not using a goodness of fit test or chi square test and it turned out that the three variables were normally distributed. The next step is testing the hypothesis by calculating the linear regression equation namely Y over X1 IS = 84,08 + 0,001 X1 meaning that the variable X1 is linier and Y and over X2 = 78,60+ 0.07 X2 means that the variable X2 is linier with Y and Y for X1 and X2 is = 2,06 + 0.30 X1 + 0.80 X2 means that variable X1 and X2 linier with Y The influence coefficient obtained is as follows : (1) The contribution coefficient of Y to X1 is 76,59% (2) The contribution coefficient of Y to X2 is 40,22% (3) The contribution coefficient of X1 over X2 is 50,73% (4) The contribution coefficient of Y to X1 and X2 is 55,81% Based on the hypothesis test, namely the significant influence test (t test) by rejecting H0 and accepting H1, we obtain : The influence of Problem Based Learning on Student learning Achievement in Citizenship Education Subjects Class XI P1 at SMA Negeri 1 Pematang Siantar T.A. 2024/2025 is “very strong” (3,7). The influence of Learning method on Student learning Achievement in Citizenship Education Subjects Class XI P1 at SMA Negeri 1 Pematang Siantar T.A. 2024/2025 is “very strong” (2,68). The influence of Problem Based Learning and Learning method on Student learning Achievement in Citizenship Education Subjects Class XI P1 at SMA Negeri 1 Pematang Siantar T.A. 2024/2025 is “very strong” (3,01).